(untitled) (Malay Literature, 2013)
The practice of nyai began in Indonesia in the 17th century when the Dutch colonizers began strengthening their foothold there. A nyai is none other than a concubine or a mistress to a foreigner, especially a European. The nyai were a group of women who were exploited during the Dutch occupation. To what extent was a nyai merely a sexual object to colonizers, and is associated with the use of force which was prevalent in the patriarchal Javanese society? Did the nyai voice their rights? Did the authorities care about their hardship? This essay shall analyse these issues using the approach of Gayatri Chakravorty Spivak’s subaltern studies, which puts foward the concept of subaltern women as oppressed women without a voice. Although others could voice the problems on their behalf, this is not the voice of subaltern women themselves as the party that voices out their problems may have other interests. This analysis is of subaltern women in Pramoedya Ananta Toer’s novel This Earth of Mankind (Bumi Manusia). This study confirms that Nyai Ontosoroh is a subaltern woman in two types of society, i.e. patriarchal and colonial society. She is manipulated for the interests of men and for colonizers. Nyai Ontosoroh can be taken to be an example of the exploitation of women in a patriarchal society. Nyai Ontosoroh herself attempts to voice out her rights as a daughter and a mother. Patriarchal and colonial groups continually deny subaltern women like Nyai Ontosoroh their rights. Keywords: subaltern women, patriarchy, nyai, colonialism